Advances in understanding the impacts of global warming on marine fishes farmed offshore: Sparus aurata as a case study. Issue 6 (29th November 2020) - Feidantsis, Konstantinos; Pörtner, Hans O.; Giantsis, Ioannis A.; Michaelidis, Basile
Abstract: Monitoring variations in proteins involved in metabolic processes, oxidative stress responses, cell signalling and protein homeostasis is a powerful tool for developing hypotheses of how environmental variations affect marine organisms' physiology and biology. According to the oxygen‐ and capacity‐limited thermal tolerance hypothesis, thermal acclimation mechanisms such as adjusting the activities of enzymes of intermediary metabolism and of antioxidant defence mechanisms, inducing heat shock proteins (Hsps) or activating mitogen‐activated protein kinases may all shift tolerance windows. Few studies have, however, investigated the molecular, biochemical and organismal responses by fishes to seasonal temperature variations in the field to link these to laboratory findings. Investigation of the impacts of global warming on fishes farmed offsore, in the open sea, can provide a stepping stone towards understanding effects on wild populations because they experience similar environmental fluctuations. Over the last 30 years, farming of the gilthead sea bream Sparus aurata (Linnaeus 1758) has become widespread along the Mediterranean coastline, rendering this species a useful case study. Based on available information, the prevailing seasonal temperature variations expose the species to the upper and lower limits of its thermal range. Evidence for this includes oxygen restriction, reduced feeding, reduced responsiveness to environmental stimuli, plus a range of molecular and biochemical indicators that change across the thermal range. Additionally, close relationships between biochemical pathways and seasonal patterns of metabolism indicate a connection between energy demand and metabolic processes on the one hand, and cellular stress responses such as oxidative stress, inflammation and autophagy on the other. Understanding physiological responses to temperature fluctuations in fishes farmed offshore can provide crucial background information for the conservation and successful management of aquaculture resources in the face of global change.